ANALISIS KOMPOSISI SUMBER CEMARAN SUNGAI DI SEKITAR TPA SAMPAH KECAMATAN TUMINTING - Zetly E. Tamod (EKOTON, 2013)
The objective was aimed to analyze whether the river polluted sources composition around the Final Management Area of waste were derived from the same sources or, not. This research was categorized in the observational study for this area. Data analyzes used both diagrams of stiff and trillinier piper. The research was concluded: (1) the distinction between river water with less polluted (Sa1) and with has mixed leacate (Sa2) was very significant from stiff diagram. The continuity form of stiff diagram emerged similarity forms, where Sa2 form tend to similar with Sa3 and Sa4, however only the Cl- anion concentration was different, meanly the river polluted sources composition was derived from the same sources; (2) projection result of the cation and anion main points showed the river water had carbonate solidification. Calcium dominant cation was at the sample point 3 and 4, bicarbonate dominant anion was at sample point 1, 2, 4, and 5, and chloride was at sample point 3.